Beneficial effects on skin health using polysaccharides from red ginseng by‐product. Issue 8 (30th June 2019) - Kim, Jong‐Eun; Jang, Seul‐Gi; Lee, Chang Hyung; Lee, Ji Yun; Park, Haenim; Kim, Jong Hun; Lee, Sihyoung; Kim, Sung Han; Park, Eun‐Young; Lee, Ki Won; Shin, Han‐Seung
Abstract: Red Ginseng is well‐known functional food in Asia which is produced by steaming and drying fresh ginseng (Panax ginseng). In the production of red ginseng extract, around 65% of the original material is left over as by‐product and discarded. Most studies on ginseng are focused on ginsenosides. Many functional substances other than ginsenoside are found in red ginseng, but they have not been studied and are usually discarded. Acidic polysaccharides, which are functional polysaccharides found in the by‐product of red ginseng, can be utilized as excellent high‐value‐added material. In this study, we developed red ginseng by‐product polysaccharides (RGBPs) by applying an enzyme‐linked high‐pressure process (ELHPP). We have demonstrated the antioxidant, anti‐aging, and anti‐atopic dermatitis efficacy of ELHPP‐RGBPs in this study. In acute oral toxicity and skin irritation tests, ELHPP‐RGBPs were found to be very low in toxicity. ELHPP‐RGBPs inhibited solar ultraviolet‐induced matrix metalloproteinase‐1 (MMP‐1) protein through activator protein‐1 (AP‐1), a major transcription factor for MMP‐1. ELHPP‐RGBP attenuated DFE‐induced AD‐like symptoms as assessed by skin lesion analyses, dermatitis score, and skin thickness. Taken together, these results suggest that ELHPP‐RGBP may have potential as a nutraceutical ingredient for skin health. Practical applications: This paper presents a new method of using ginseng by‐product that has not been used and discarded. The use of polysaccharides in ginseng by‐product has been shown to prevent skin wrinkles and atopic dermatitis. This is an economical new functional food material.